The influence of corporate social responsibility on consumer purchasing behaviour - Min, Yew Qi; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2022)
This study was conducted to investigate the influence of corporate social responsibility (CSR) on consumer purchasing behaviour. The method of systematic sampling was used, and a total of 150 students participated as respondents. A five-point Likert scale were utilised to measure the independent variables (economic responsibility, legal responsibility, ethical responsibility and philanthropic responsibility) and dependent variable (consumer purchasing behaviour) respectively. The data were collected by using online self-administered questionnaires. The Pearson correlation coefficient results indicated that economic responsibility, legal responsibility, ethical responsibility and philanthropic responsibility were significantly and positively correlated to the consumer purchasing behaviour. In addition, the results of Multiple Linear Regression showed that the four the independent variables could explain 42.0% of consumer purchasing behaviour, with ethical responsibility having the greatest influence on consumer purchasing behaviour. The findings of this study could aid consumers and businesses in comprehending the impact of corporate social responsibility on consumer purchasing behaviour.